ANALYSIS OF FACTORS AFFECTING THE SUCCESS OF SELF-REGULATED LEARNING IN WORKING UNIVERSITY STUDENTS - Fauzi, Ahmad; Situmorang, Robinson; Chaeruman, Uwes Anis (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This research aims to analyze the internal and external factors influencing the success of Self-Regulated Learning (SRL) in university students who are also actively working. Self-regulated learning is defined as an individual's ability to actively and autonomously manage their learning process, including goal setting, self-monitoring, and strategy adjustment. In the context of working students, successful self-regulated learning is crucial given the dual challenges they face. The proposed methodology is a mixed-methods approach, beginning with a qualitative phase (in-depth interviews) to explore experiences and strategies, followed by a quantitative phase (questionnaires and academic data) to measure the relationships between variables such as self-efficacy, achievement motivation, cognitive and metacognitive strategies, emotional regulation, time management, work intensity, social support, learning environment, and access to and utilization of technology. Anticipated findings suggest that high self-efficacy, strong intrinsic motivation, adaptive time management strategies, adequate social support, and a conducive learning environment are important predictors of successful self-regulated learning. The practical implications of this research are expected to provide recommendations for students to improve their SRL skills and for educational institutions to develop more effective support.